Innovation of Audio-Visual Teaching Materials in Pancasila Education Learning in Elementary Schools to Enhance Student Learning Participation - Natalia, Gloria; Pratomo, Wachid; Andini, Dinar Westri (Jurnal Sains Sosio Humaniora, 2026)
This study aims to describe the use of audio-visual teaching materials in Pancasila Education learning at the elementary school level and to examine their role in enhancing students’ learning participation. The study employed a qualitative approach with a descriptive research design. The participants consisted of Pancasila Education teachers and elementary school students involved in learning activities utilizing audio-visual teaching materials. Data were collected through observation, interviews, and documentation, and were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings revealed that the use of audio-visual teaching materials created a more engaging, interactive, and contextual learning environment. Through the utilization of instructional videos, animations, and other visual media, students became more actively involved in the learning process, as indicated by increased attention, confidence in asking questions, ability to express opinions, and participation in group discussions. Furthermore, audio-visual teaching materials helped students understand Pancasila values more concretely, as the content was presented through examples closely related to their daily lives. Although several challenges were identified, particularly regarding the availability of technological facilities and the preparation of learning media, the use of audio-visual teaching materials proved effective in supporting student-centered learning and optimizing student participation. Therefore, innovation in audio-visual teaching materials can serve as an alternative strategy for improving the quality of Pancasila Education learning in elementary schools.